Quraish Shihab’s Tafsir of QS. 'Abasa (80): 1-10: Rethinking Disability In Contemporary Context - Idris, Muhammad; Hajar, Siti; Achmad, Adang Darmawan; Huda, Muhammad Khozinul; Qotadah, Hudzaifah Achmad (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This study explores the contextual interpretation of QS. ‘Abasa (80): 1-10 as articulated by Quraish Shihab in his renowned work, tafsir al-misbah. The surah recounts an incident where the Prophet Muhammad (SAW) frowned and turned away from Abdullah bin Ummi Maktum, a visually impaired companion. This narrative serves as a critical foundation for discussing issues of equality and the rights of persons with disabilities within an Islamic framework. Employing a qualitative research methodology with descriptive analysis, this study examines primary and secondary data to uncover the modern applicability of these verses in addressing contemporary discrimination against persons with disabilities. The findings reveal that QS. ‘Abasa emphasizes the principles of equality and inclusivity, advocating for the realization of the rights of persons with disabilities in a manner commensurate with those of the broader society. The study concludes that a modern interpretation of QS. ‘Abasa can serve as a philosophical foundation for fostering a more just and equitable society, underscoring that piety (taqwa) is the sole criterion for human distinction in the eyes of Allah.